Survey for Enterobacteria and Vibrio spp. Associated with Irrigated Vegetables in Irrigation Areas of Northern Bauchi State, Nigeria - Dahiru, Umar; Mukhtar, M.D.; Yusuf, Ibrahim; Ahmed, Yusuf (Journal of Biochemistry, Microbiology and Biotechnology, 2024)
This study was prompted in a bid to determine the level of public health hazards associated with the presence of enterobacteria and Vibrio spp. in irrigated vegetables in irrigation areas of Northern Bauchi State, Nigeria. This was to address the question of what the recent circumstances behind the report of outbreak of gastroenteritis in the region were, thus the impetus for the current investigation. Irrigation Water and irrigated vegetable samples (72) from across the four local government areas were collected from different irrigation sites and analysed for bacteriological contamination indices. The River Zaki, River Jama’are, and River Zigau were observed to be the primary sources of irrigation water. The overall mean aerobic mesophilic count and the Most Probable Number values for coliforms observed in this study ranged from 1.6x104 to 8.x108 Cfu/mL and 14 to 33, respectively. Up to 62 isolates comprising 42 (81.82%) enterobacterial strains, eight Pseudomonas spp. and ten representing vibrio spp. were isolated from the analysis of vegetables and irrigation water samples. In descending order of dominance, the organisms isolated were E. coli 14 (22.6%), Vibrio spp. 10 (16.1%), Citrobacter spp. 9 (14.5%), Pseudomonas aeruginosa 8 (12.9), Salmonella enterica 8 (12.9%), Klebsiella oxytoca 8 (12.9%) and Klebsiella pneumoniae 5 (8.1%). All the isolates were sensitive to most of the antibiotics used except ampicillin (10 µg) and amox-clav (30 µg). No resistance was recorded against ciprofloxacin (5 µg). The findings revealed that the river water used for irrigation in this study was a possible pre-harvest source of contamination of fresh vegetables, potentially constituting a health risk to consumers.